Clinicopathological characteristics of KIT and protein kinase C‐δ expression in adenoid cystic carcinoma: comparison with chromophobe renal cell carcinoma and gastrointestinal stromal tumour. Issue 4 (2nd August 2017) - Park, Cheol Keun; Kim, Won Kyu; Kim, Hoguen
Abstract : Aims: KIT overexpression is frequently observed in adenoid cystic carcinomas (AdCCs), chromophobe renal cell carcinomas (ChRCCs), and gastrointestinal stromal tumours (GISTs). Persistent KIT activation has been reported to be mediated by protein kinase C (PKC)‐δ in a subset of colon cancers with wild‐type KIT overexpression, and by PKC‐θ in GISTs with mutant KIT overexpression. To elucidate the clinical implications of PKC‐δ and PKC‐θ expression in KIT‐expressing tumours, we investigated the expression of KIT, PKC‐δ and PKC‐θ in AdCCs and ChRCCs in comparison with GISTs. Methods and results: KIT expression, PKC‐δ expression and PKC‐θ expression were analysed in whole sections from 41 AdCCs, 40 ChRCCs and 56 GISTs by immunohistochemistry. Membranous expression of KIT was found in 34 AdCCs and all ChRCCs, whereas cytoplasmic expression of KIT was found in 46 GISTs. In AdCCs, PKC‐δ expression was associated with histological grade ( P = 0.049), lymphovascular invasion ( P = 0.004), perineural invasion ( P = 0.002), and KIT positivity ( P = 0.002). PKC‐δ positivity was associated with shorter relapse‐free survival (RFS) ( P = 0.017) and a tendency for there to be shorter overall survival (OS) ( P = 0.090) in patients with AdCCs. No clinicopathological associations were observed between PKC‐δ and KIT expression in ChRCCs. In GISTs, PKC‐θ expression was associated with higher mitotic count ( P = 0.011) and high grade according to the modified National Institutes of Health criteria ( P < 0.001). PKC‐θ positivity was associated with shorter RFS ( P = 0.016) and a tendency for there to be shorter OS ( P = 0.051) in patients with GISTs. Conclusions: PKC‐δ expression is associated with KIT expression and the prognosis of patients with AdCCs, suggesting that PKC‐δ may be a potential therapeutic target for AdCCs.